Analysis of hydrodynamic performance and structural parameter impacts of biplane-type otter board based on smoothed particle hydrodynamics method - Chu, Wenhua; Zhao, Zijing; Guo, Huiqin; Yan, Jifeng (Frontiers in Mechanical Engineering, 2025)
In trawling fisheries, otter boards are essential tools that expand net openings and gather fish schools. This study uses the Smoothed Particle Hydrodynamics (SPH) method to create a three-dimensional numerical model for a biplane-type otter board. A scaled model is fabricated for dynamic flume experiments, validating the numerical results. Analysis with Computational Fluid Dynamics (CFD) demonstrates that the three-dimensional SPH model enhances computational accuracy over traditional CFD. A comprehensive analysis of hydrodynamic performance under various structural parameters, including camber ratio and the position of maximum camber ratio, was conducted. Results indicate that both the camber ratio and its position significantly affect the hydrodynamic performance. For maximum lift coefficient, setting the camber ratio of both boards to approximately 20% is optimal. However, for a higher lift-to-drag ratio, a 5% camber ratio for both boards is preferable. When the position of maximum camber ratio is at 10%, the lift coefficient peaks, offering the best expansion effect. Conversely, setting this position at 30% maximizes the lift-to-drag ratio, indicating better overall performance. This study provides valuable insights for optimizing otter board design in trawling fisheries.